Stimulatory Effect of Tofacitinib on Bone Marrow Adipocytes Differentiation - Letarouilly, Jean-Guillaume; Paccou, Julien; Badr, Sammy; Chauveau, Christophe; Broux, Odile; Clabaut, Aline (Frontiers in Endocrinology, 2022)
Background: Systemic inflammation is the main factor underlying secondary osteoporosis in patients with rheumatoid arthritis (RA). Janus kinase inhibitors (JAKi), such as tofacitinib (Tofa), can control systemic inflammation and may have beneficial effects on bone in various models. This might be due to direct effects on the bone microenvironment and not exclusively based on their anti-inflammatory function. Bone marrow adipocytes (BMAds) are abundant in the bone microenvironment. The effect of JAKi on BMAds is unknown, but evidence suggests that there is competition between human bone marrow-derived stromal cell (hBMSC) differentiation routes towards BMAds and osteoblasts (Ob) in osteoporosis. Objectives: To determine whether Tofa influences BMAds and Ob derived from hBMSCs. To investigate the potential effects of Tofa on bone marrow adiposity in RA patients. Methods: To determine the effect of Tofa on cellular commitment, BMAds and OB derived-hBMSCs were cultured for 3 days together with Tofa at 200, 400 or 800 nM and TNFα. This study was also conducted using mature BMAds. The impact of Tofa was determined by gene and protein expression analysis, and cell density monitoring. In parallel, in a pilot study of 9 RA patients treated with Tofa 5 mg twice a day (NCT04175886), the proton density fat fraction (PDFF) was measured using MRI at the lumbar spine at baseline and at 6 months. Results: In non-inflammatory conditions, the gene expression of Runx2 decreased in Ob treated with Tofa (p<0.05). The gene expression of PPARγ2, C/EBPα and Perilipin 1 were increased compared to controls (p<0.05) in BMAds treated with Tofa. Under inflammatory conditions, Tofa did not change the expression profiles of Ob compared to TNFα controls. In contrast, Tofa limited the negative effect of TNFα on BMAd differentiation (p<0.05). An increase in the density of differentiated BMAds treated with Tofa under TNFα was noted (p<0.001). These findings were consolidated by an increase in PDFF at 6 months of treatment with Tofa in RA patients (46.2±7.0% versus 53.2±9.2% p<0.01). Conclusion: Together, these results suggest a stimulatory effect of Tofa on BMAd commitment and differentiation, which does not support a positive effect of Tofa on bone.